Respuesta :
Answer:
x=2
Step-by-step explanation:
13x - 2(8+5x) = 12 - 11x
The first step is to distribute the -2
13x -2*8 -2*5x = 12-11x
13x -16-10x = 12-11x
Combine like terms
3x-16 = 12-11x
Add 11x to each side
3x+11x -16 = 12-11x+11x
14x-16 = 12
Add 16 to each side
14x-16+16 = 12+16
14x=28
Divide by 14
14x/14 =28/14
x =2
Answer:
x = 2
Step-by-step explanation:
13x - 2(8 + 5x) = 12-11x
Distribute
13x -16 - 10x = 12 - 11x
Combine like terms
3x - 16 = 12 - 11x
Addition property of equality
3x = 28 - 11x
Addition property of equality
14x = 28
Divison property of equality
x = 2